Tunable and compact permanent magnet uniform spreading beamline for electron irradiation accelerators - Zijian Zhou; Keyan Sheng; Zhenyi Zhang; Mianzhi Xiong; Haozhe Li; Jiang Huang (Physical Review Accelerators and Beams, 2023)
The growing interest in the field of electron irradiation accelerators has led to various research opportunities, with a crucial emphasis on enhancing the irradiation homogeneity of accelerators to advance the industry of the irradiation process. In this study, we introduce a tunable and compact uniform spreading beamline that comprises a permanent magnet quadrupole doublet and an electron beam permanent magnet spreading system. This beamline could solve the problem of poor irradiation homogeneity caused by irregular beam spots in electron irradiation accelerators. Flexible and tunable magnetic yokes enable rapid changes to the magnetic field distribution based on different beam spot profiles or irradiation processing requirements, achieving uniform spreading of different beam spots and improving irradiation homogeneity. Additionally, we evaluated the performance of rectangular permanent magnet poles to minimize errors in future accelerator applications. The implementation of this beamline enhances irradiation quality and provides an experimental foundation for further investigating the interaction between electron beam irradiation rates and materials.